Method of Genetic Algorithms for the Optimal Investment Portfolio - Mekush, Oksana H.; Kuzmych, Olena I.; Solich, Kateryna; Telmoudi, Achraf; Мекуш, Оксана Григорівна; Кузьмич, Олена Іванівна; Соліч, Катерина; Телмоуді, Ачраф (IEEE, 2018)
This paper is devoted to the problem of optimal investment portfolio design on the base of mathematical modeling tools and method of genetic algorithms. The purpose relates to investing the funds into financial assets such that certain requirements regarding the expected profits and possible losses would be reached. The main result is developing a state-space dynamical model of portfolio management and applying a genetic algorithm in order to obtain the optimal solution.
Keywords: Genetic Algorithms; Optimal Investment Portfolio